81 Inclusion of PD-L1-expressing tumor cells in the combined positive score algorithm yields superior identification of positive specimens around diagnostic cut-offs across multiple indications. (9th November 2020) - Milo, Jay; LaPlaca, Christopher; Hand, Julia; Hund, Stephanie; Apostolaki, Angeliki; Guerrero, Lindsay; Emancipator, Kenneth; Juco, Jonathan; Portier, Bryce; Tabuena-Frolli, Siena; Kulangara, Karina
Abstract : Background: PD-L1 IHC 22C3 pharmDx uses Tumor Proportion Score (TPS) and Combined Positive Score (CPS) scoring algorithms for the immunohistochemical (IHC) evaluation of PD-L1 protein expression in human cancer tissues; both algorithms include PD-L1 staining tumor cells (TC) in scoring and CPS also includes scoring of PD-L1 staining mononuclear inflammatory cells to aid in the identification of patients for treatment with pembrolizumab (KEYTRUDA®) using indication-specific diagnostic cut-offs. This study evaluated contribution of TC in determining specimen diagnostic status based on the CPS scoring algorithm by looking into four tumor indications approved for use with KEYTRUDA®: gastric or gastroesophageal junction (GEJ) adenocarcinoma (GC/GEJ), urothelial carcinoma (UC), head and neck squamous cell carcinoma (HNSCC), and esophageal squamous cell carcinoma (ESCC). Detection of specimens expressing PD-L1 is significantly dependent on the PD-L1 staining TC component. Methods: A retrospective analysis was done looking at Dako's internal tumor bank of the mentioned indications that were all stained with PD-L1 IHC 22C3 pharmDx and scored using the TPS, CPS and Quantitative Immune Cell Density (QID) methods described in figure 1 . Statistical analysis encompassed looking at the scores generated that met the following criteria: CPS>0, TPS>0 and CPS≠TPS and then evaluating the percentage of those samples that changed from positive to negative diagnostic status upon removal of the TC component from the scoring. Results: A noticeable downward trend was observed in all four indications in the total number of positives with the removal of the TC component. Table 1 aptly captures this by showing the number of specimens for each indication that had changed from positive to negative around each indication's diagnostic cut-off(s). The three indications that showed the highest percentages of diagnostic status change were HNSCC (CPS ≥20) with a remarkable 83.3% (130) followed by UC (CPS ≥10) at 46.3% (57) and ESCC (CPS ≥10) at 36.6% (45) of the specimens reclassified as negative. Conclusions: PD-L1 IHC 22C3 pharmDx (Dako, USA) stains both TC and immune cells. Removal of the PD-L1 staining TC from the CPS algorithm reduces the number of specimens scored as positive for each indication's respective diagnostic cut-off(s). Scoring only IC reduces the number of specimens scored as positive for each indication's respective cutoff.